Self-directed learning: The impact among medical students - Deepak Anil; Sunil Kumar D; M R Narayana Murthy (Zanjan University of Medical Sciences and Health Services, 2023)
Background & objective: Self-directed learning (SDL) has grown popular in the medical curriculum and is recommended as an effective learning approach for medical students. As medical research is continuously changing and information is exploding, it is critical to prepare doctors for SDL. The present study aimed to assess the impact and perception of SDL among medical students. Materials & methods: This longitudinal study was done among 131 first-year medical students for 2 months. A poster competition was conducted and the students were asked to give their feedback through an online Google form, one week after the competition. Descriptive statistics were applied and analyzed using SPSS software. The location of the participants was obtained, and the geographical data were analyzed in the Quantum Geographical Information System (QGIS). Results: Among the 131 study participants, 61.8% were female. Almost 94.7% of participants informed SDL was a helpful learning approach and 97.7% informed it had helped them learn at their own pace. SDL exercises also helped the participants determine their level of readiness to learn (52.67%), set learning goals (56.48%), engage in the learning process (75.57%), and evaluate their learning (47.33%). Conclusion: SDL was deemed beneficial by the majority of participants in terms of grasping the subject and studying at their own speed. Studies correlating the SDL perception and the student's academic performance are lacking, which makes it difficult to predict their success in the upcoming exams. As a result, additional research is needed in this area.